ANALISIS PROJECT BASED LEARNING TERHADAP UMKM MIRROR GALLERY BANTUL DALAM MEMPERTAHANKAN RANTAI PASOKAN (Studi Kasus UMKM atau Perusahaan Mirror Gallery Bantul) - Janah, Anisa Wardatul; Sari, Selvia Nur Rohmah; Mahabbah, Luthfia Nisfi; Rahmawati, Umi Widya (Journal Financial, Business and Economics, 2024)
Green supply chain management has attracted the attention of academics and entrepreneurs as environmental issues grow. This research aims to find out how global supply chain management is carried out in the Bantul mirror gallery company. This research uses a qualitative research approach. Data collection through interviews and the company's official website. The results show that the company has been running according to the Company's Operational Standards (SOP), besides that the company also continues to make changes and evaluations to maintain customer loyalty. Of course, the Mirror Gallery company not only focuses on products, quality, and quantity, but also the sense of trust that is built as well as a sense of concern for reducing production waste that is used excessively. In addition, there is a lack of promotional media because the company only relies on websites and emails. Another study conducted in Bantul Regency also highlighted the influence of supply chain management on competitive advantage and company performance, particularly in small and medium enterprises. The results of these various studies can provide useful insights for entrepreneurs and academics regarding the importance of supply chain management in improving company performance and competitiveness.